2019
DOI: 10.37287/jppp.v2i3.134
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Work Motivation Towards Caring Behaviour of Nurse at the Inpatient Ward of Class III

Abstract: Caring merupakan suatu dasar penting yang dijadikan sebagai inti dalam seluruh proses praktik keperawatan dengan cara meningkatkan kepedulian serta pendekatan dinamis guna membantu proses kesembuhan pasien yang salah satunya dipengaruhi oleh motivasi kerja. Motivasi kerja menjadi faktor penting bagi perawat dalam menjalankan perannya sebagai pelaksana asuhan keperawatan. Penelitian ini bertujuan untuk mengetahui hubungan motivasi kerja dengan perilaku caring perawat, menggunakan metode kuantitatif dengan desai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…As for the personality aspect, a high locus of internal control and self-concept often shows a high degree of work motivation; however, it was also found that individuals who are fit and have cognitive abilities tend to find routine tasks boring and this lowers their level of motivation to work. According to Purwanti et al (2020), the differences between male and female workers also depend on job factors (autonomy, use of skills, career development opportunities, status and salary), family factors (responsibility for family burdens) and social factors (education, age, religion and degree) can also influence work motivation differences between gender. In addition, Gunawan et al (2019) stated that female workers will be more motivated to work than men if the aforementioned factors were evenly distributed among them.…”
Section: Self-motivation On the Effective Job Performancementioning
confidence: 99%
“…As for the personality aspect, a high locus of internal control and self-concept often shows a high degree of work motivation; however, it was also found that individuals who are fit and have cognitive abilities tend to find routine tasks boring and this lowers their level of motivation to work. According to Purwanti et al (2020), the differences between male and female workers also depend on job factors (autonomy, use of skills, career development opportunities, status and salary), family factors (responsibility for family burdens) and social factors (education, age, religion and degree) can also influence work motivation differences between gender. In addition, Gunawan et al (2019) stated that female workers will be more motivated to work than men if the aforementioned factors were evenly distributed among them.…”
Section: Self-motivation On the Effective Job Performancementioning
confidence: 99%